2018
DOI: 10.3389/fimmu.2018.01576
|View full text |Cite
|
Sign up to set email alerts
|

Plasmatic Levels of IL-18, IP-10, and Activated CD8+ T Cells Are Potential Biomarkers to Identify HIV-1 Elite Controllers With a True Functional Cure Profile

Abstract: Elite controllers (ECs) are rare individuals able to naturally control HIV-1 replication below the detection limit of viral load (VL) commercial assays. It is unclear, however, whether ECs might be considered a natural model of a functional cure because some studies have noted CD4+ T cell depletion and disease progression associated with abnormally high levels of immune activation and/or inflammation in this group. Here, we propose the use of immunological parameters to identify HIV-1 ECs that could represent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…S1A,B; Wherry et al 2007). Altogether this strengthens the previous suggestion that accumulative virus loads rather than the virus load per se determine the observed differences in the immune responses and infection fates (Bocharov 1998;Côrtes et al 2018).…”
Section: Spleen Gene Coexpression Network In Acute and Chronic Viralsupporting
confidence: 86%
“…S1A,B; Wherry et al 2007). Altogether this strengthens the previous suggestion that accumulative virus loads rather than the virus load per se determine the observed differences in the immune responses and infection fates (Bocharov 1998;Côrtes et al 2018).…”
Section: Spleen Gene Coexpression Network In Acute and Chronic Viralsupporting
confidence: 86%
“…Several studies have shown that HIC exhibit cellular and serological markers of immune activation and inflammation despite a spontaneous control of HIV replication (21-24). However, no evidence of persistent inflammation was observed when HIC were defined using stringent criteria in relation to the cutoff level of viremia (Յ50 copies/ml) and a minimum follow-up time of Ͼ5 years, compared to HIV-uninfected subjects (25). We found here that, compared to cART patients, the level of inflammatory gene expression remains still dramatically reduced in HIC with a significant downregulation of TLRs, TRIM1, and CXCL8/IL-8.…”
Section: Discussionmentioning
confidence: 53%
“…Besides, increased oxidative stress during HIV-1 infection, rising either directly from the virus or indirectly from HIV-related inflammation, supports the activation of latently HIV-1-infected cells (13). Less is known about the role of inflammation in EC, although some studies, including an earlier study from our group, suggest that gene expression and/or levels of inflammatory markers are low and comparable to HIV-uninfected individuals (3,19,20). In contrast, one study reported increased levels of inflammatory markers in EC(4).…”
Section: Discussionmentioning
confidence: 76%